Self-assessment: An essential skill for learning and performance in the workplace - Catherine Marienau (Adult Education Research Conference, 1994)
Using qualitative methodology, the study examined perspectives of working professionals concerning the role and value of self-assessment in their professional lives. Content analysis revealed six major themes concerning the benefits of self-assessment in relation to workplace learning, workplace performance, and personal and professional development.